2023
DOI: 10.1136/bmj-2022-074589
|View full text |Cite
|
Sign up to set email alerts
|

Increased cardiovascular disease risk after exposure to low dose radiation

Abstract: These risks should now be considered in radiation protection measures and policies

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…A newly published meta-analysis of updated epidemiological data has emphasized more than before the close association between chronic low-dose radiation exposure and CVD [ 7 ]. The analysis showed that low dose radiation and/or low dose rate exposures are associated with an increased risk of CVD per unit dose [ 8 ]. However, underlying molecular mechanisms of CVD caused by chronic low dose rate exposure are not fully known.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A newly published meta-analysis of updated epidemiological data has emphasized more than before the close association between chronic low-dose radiation exposure and CVD [ 7 ]. The analysis showed that low dose radiation and/or low dose rate exposures are associated with an increased risk of CVD per unit dose [ 8 ]. However, underlying molecular mechanisms of CVD caused by chronic low dose rate exposure are not fully known.…”
Section: Discussionmentioning
confidence: 99%
“…The association between CVD and chronic low-dose exposure has been further corroborated by a new comprehensive meta-analysis performed on more recent epidemiological data [ 7 ]. The analysis suggested a higher relative risk per dose unit at low doses and low dose rates [ 7 , 8 ]. However, unlike exposures to high doses, little is known about the biological mechanisms of CVD caused by chronic low doses and low dose rates, such as occupational exposure.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, it is well-established that high doses of IR, such as those used for radiotherapy can produce direct damage to the heart and arteries, leading to an increased risk of CVD [5][6][7]. However, evidence is emerging that IR exposure may also increase the long-term risk of cardiovascular effects even at low levels of doses less than 0.1 Gray (Gy) or 0.1 sievert (Sv; 1 Sv is equivalent to Gy in medical imaging because the radiation weighting factor for X-rays and gamma rays is 1.0), which are characteristic of doses from medical diagnostic exposures [8,9]. Indeed, the association between CVDs and low-dose exposure has been recently confirmed by a large comprehensive meta-analysis performed on 93 cohort studies, including individuals who had been exposed to radiation in various settings (mostly radiotherapy and occupational exposures, but also diagnostic radiology and environmental exposures).…”
Section: Low-dose Ionizing Radiation and Cardiovascular Diseasementioning
confidence: 99%